Entropy generation due to natural convection of a nanofluid in a partially open triangular cavity - Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier Science Bv, 2017)
A numerical analysis of laminar natural convection with entropy generation in a partially heated open triangular cavity filled with a Cu-water nanofluid has been carried out. Mathematical model including partial differential equations and boundary conditions has been solved by using finite difference method. Particular efforts have been focused on the effects of Rayleigh number, nanoparticles volume fraction and position of the local heater on streamlines, isotherms, local entropy generation as well as local and average Nusselt number, average Bejan number, average entropy generation and fluid flow rate. Obtained results have demonstrated that the heat transfer enhancement and fluid flow attenuation with nanoparticles volume fraction, mainly for high values of Rayleigh number. (C) 2016 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Natural convection; Nanofluid; Partially open traingular cavity; Local heat source